2006
DOI: 10.1111/j.1365-2672.2006.02927.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH, temperature and substrate on N2O, NO and CO2 production by Alcaligenes faecalis p.

Abstract: Aims:  To study the effect of pH, temperature and substrate on the magnitude of N2O and NO production by heterotrophic nitrifiers. Methods and Results:  The change in N2O and NO production by the heterotrophic nitrifiers Alcaligenes faecalis subsp. parafaecalis and Paracoccus pantotrophus because of variations in pH, temperature and substrate was studied in chemostat cultures under steady‐state conditions. N2O, NO and CO2 production increased with temperature between 4 and 32°C. For N2O an optimum temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 56 publications
9
47
1
Order By: Relevance
“…It is well known that the optimal temperature range of heterotrophic nitrification-aerobic denitrification bacteria was 25°C-37°C (Kesik et al, 2006;Taylor et al, 2009;Guo et al, 2013b). According to our experiments, as shown in Fig.…”
Section: Low Temperature Shockmentioning
confidence: 78%
“…It is well known that the optimal temperature range of heterotrophic nitrification-aerobic denitrification bacteria was 25°C-37°C (Kesik et al, 2006;Taylor et al, 2009;Guo et al, 2013b). According to our experiments, as shown in Fig.…”
Section: Low Temperature Shockmentioning
confidence: 78%
“…It is well known that low pH decreases the activity of the N 2 O-reductase, thereby increasing production of N 2 O from denitrification (Nömmik, 1956;Weier and Gillam, 1986;Granli and Bockman, 1994). For nitrification, it has also been demonstrated that low pH values favor N 2 O production (Sitaula and Bakken, 1993;Martikainen and De Boer, 1993;Kesik et al, 2006). Furthermore, it has been shown by Kiese and Butterbach-Bahl (2002) that low pH was a crucial factor driving high N 2 O emissions from coastal lowland soils in an Australian rainforest.…”
Section: Claymentioning
confidence: 99%
“…This is in line with results of others who found exponential relationships between soil NO fluxes and soil temperatures for agricultural (Williams et al, 1998;Roelle et al, 2001) as well as for forest soils (Van Dijk and Meixner, 2001;Schindlbacher et al, 2004). The strong temperature response of soil NO fluxes at our site may not only be due to the stimulation of nitrification as the assumed main process of NO production at our site , but may also be explained by increasing contributions of NO production by chemo-denitrification in the acidic organic layer (pH of forest floor ≤3.2) at increasing temperatures (Kesik et al, 2006). In agreement with other field and laboratory studies (Smith et al, 1998;Dobbie and Smith, 2001;Schindlbacher et al, 2004), which reported that not only nitric oxide but also nitrous oxide emissions increased exponentially with soil temperature, also our long-term dataset shows that N 2 O emissions increase exponentially with temperature if freeze-thaw periods are excluded.…”
Section: No and N 2 Omentioning
confidence: 99%